Investigating Supported Decision‐Making for Persons With Mild to Moderate Intellectual Disability Using Institutional Ethnography. Issue 2 (3rd November 2019) - Devi, Nandini; Prodinger, Birgit; Pennycott, Andrew; Sooben, Roja; Bickenbach, Jerome
Abstract: Making one's own choices is an important part of leading a fulfilling life within society. However, people with IDs often face significant obstacles when making their own decisions. Article 12 (Equal recognition before the law) of the United Nations Convention on the Rights of Persons with Disabilities (CRPD) aims to ensure firstly that people with IDs and others with compromised capacity are nonetheless recognized as legal individuals, and secondly that assistance is provided in the form of supported decision‐making in order to exercise this resulting legal capacity. It is unclear whether current national legislation in any country satisfies these requirements in practice. This study utilizes institutional ethnography to reveal how decision‐making is coordinated in practice for people with mild to moderate IDs living in supported residential environments in England, and to determine whether these processes are compliant with Article 12 of the CRPD. Data collection was based on observations, semi‐structured interviews, and documentary analysis, involving 29 participants including people with mild to moderate IDs. The results point to the complexity of supported decision‐making and identify three main categories of decision‐making: spontaneous decisions, mid‐term decisions, and strategic decisions. The data also show that people with mild to moderate IDs are able to exercise their legal capacity through support decision‐making in their everyday life. Immediate and informal supported decision‐making exists in daily practice for people with mild to moderate IDs living in supported residential environments. Although there are structures in place for implementing supported decision‐making, various barriers persist that limit the overall efficacy and consistency of the realization of supported decision‐making, for example, multiple use of mental capacity assessments. Such practices move away from the supported decision‐making model toward substituted decision‐making.